ANALISIS KEMUDAHAN MELAKUKAN PEMBAYARAN, ABILITY TO PAY DAN KEPATUHAN PEMBAYARAN IURAN PESERTA MANDIRI JAMINAN KESEHATAN NASIONAL: STUDI PADA PESERTA MANDIRI BPJS KESEHATAN KANTOR CABANG MAGELANG (2020 - Ossy Murpratiwi; Nugroho Teguh Benianto; Sujoko (FEB Universitas Maritim Semarang, 2022)
This study aims to analyze the ease of making payments, ability to pay and compliance with making payment of the individual participant National Health Insurance (JKN-KIS) in the BPJS Kesehatan Magelang. This research, it is hoped that it will be able to contribute to BPJS Kesehatan regarding matters and ideas to form a strategy which can increase the collectability of JKN-KIS premium payment contributions, especially for the individual participant segment. This research belongs to the type of quantitative descriptive research. The data used in this study are primary data and secondary data. The data were collected through distributing questionnaires given to 400 individual participants BPJS Kesehatan. The data collection method in this study used a questionnaire using a Likert scale. The data that has been collected through distributing questionnaires, then testing the instrument. Where, the instrument test consists of validity and reliability tests. Researchers in this study took samples using purposive sampling technique, specifically for individual participants BPJS Kesehatan. This research uses quantitative descriptive analysis by calculating the average (mean). The results of the analysis show that the ease of making payments shows the dimensions mean high category in all dimensions, so it can be concluded that the participants are very easy to make contribution payments with the payment mechanisms and procedures and channels provided by BPJS Kesehatan. The results analysis of the ability to pay and the results analysis of compliance with making payments show the dimensions mean value of the low category in all dimensions. That it needs to receive special attention from BPJS Kesehatan so the ability and compliance in paying contributions will increase.